Nondimensional translational characteristics of elastomer components / Andreas Dutzler, Christian Buzzi and Martin Leitner - Dutzler, Andreas; Buzzi, Christian; Leitner, Martin (Smart Manufacturing Research Institute (SMRI), 2021)
Elastomer components are used in both primary and secondary spring stages in bogies of rail vehicles. The design of spring components of a bogie requires knowledge of the calculation of the elastic properties of these components. An elastomer spring component is typically analyzed in the dimension to be investigated. Calculated force-displacement curves are directly related to the material and dimension of the component itself. The objective of this paper is to establish generalized or, in other words, universally valid force-displacement characteristics by breaking the entanglement with component size. The advantage of this approach is the extended validity of the results for a specific spring shape of any size. The simulations are performed only once for each shape and may be converted to any other size using the proposed methodology. A numerical study of a layer spring with rectangular cross-sectional area and fixed edges on both top and bottom sides serves as a reference example.